Field progeny testing of Frieswal bulls - Retrospective and perspective - DAS, A K; KUMAR, RAVINDER; SINGH, UMESH; KUMAR, SUSHIL; RAJA, T V; SIROHI, A S (The Indian Journal of Animal Sciences, 2022)
Young Frieswal bulls (334; cross of HF and Sahiwal) were put under test mating in 16 different sets at four states located in varied agro-climatic conditions of India. Daughters born up to 12th set of bull who had completed their first lactation 305 days milk yield were evaluated. Total 469,501 artificial inseminations were performed in the project, of which 410,163 AI followed and 184,598 pregnancies confirmed amounting to an overall conception rate of 45%. Total 58,168 female calves were born, of which 17,107 reached age at first calving till 2020. Total 233 bulls have so far been evaluated on the basis of 9,680 daughters first lactation 305 day milk yield records showing an increasing trend in breeding values from first set (1958.0±26.90) to last evaluated set (3429.84±48.13). Through the intervention of Field Progeny Testing programme of this Institute, the average first lactation 305 days milk yield of the Frieswal progenies in the adopted villages had increased by 60.35% in KVASU-Thrissur, 42.86% in GADVASU-Ludhiana, 10.9% in BAIF-Pune and 41.64% in GBPUA&T, Pantnagar unit. Further, the average age at first calving (AFC) of the Frieswal progenies had also reduced by 12.87% in KVASU, 21.71% in GADVASU, 1.9 % in BAIF and 9.29 % in GBPUA&T unit.